2020
DOI: 10.18083/lcappl.2020.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Characteristics of Liquid Crystal Cell with WS2 Nanoparticles: Mesophase Sensitization and Relief Features

Abstract: В настоящей работе рассмотрены временны́е параметры (время реакции и релаксации среды) жидкокристаллической ячейки, сенсибилизированной наночастицами WS 2 и сконструированной с учетом модификации проводящего покрытия ITO углеродными нанотрубками. Углеродные нанотрубки осаждались на поверхность проводящего слоя вертикально с применением лазерного метода и ориентационного воздействия электрического поля с напряженностью 600 В/см. Использование двух управляющих функций, а именно процесса сенсибилизации объема мез… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…It was found that the stabilization of such solutions is possible with the use of surfactants [11,12], ultrasonic [13] or laser [14] treatment of the solution. It is assumed that a similar effect on the stability of solutions can be observed in the another anisotropic systems [15][16][17][18].…”
Section: Introductionmentioning
confidence: 93%
“…It was found that the stabilization of such solutions is possible with the use of surfactants [11,12], ultrasonic [13] or laser [14] treatment of the solution. It is assumed that a similar effect on the stability of solutions can be observed in the another anisotropic systems [15][16][17][18].…”
Section: Introductionmentioning
confidence: 93%
“…В настоящей работе при многократных наблюдениях установлены корреляционные зависимости между спектральными параметрами, концентрацией наночастиц, углом подвеса молекул сенсибилизированного ЖК на подложке и временными характеристиками ячейки на основе системы: ЖК-наночастицы WS 2 . Стоит обратить внимание, что данная работа является логическим продолжением исследований, начатых для системы ЖК-WS 2 наночастицы, представленных ранее в публикации [22].…”
Section: Introductionunclassified
“…For the development of modulation devices, as optical limiters, wavefront correctors, spatial-light modulators, and other components based on ITO [8] [9][10] [11], high transmittance level and small signal-to-noise ratio are required. In this case, one of the main issues for the device development is to decrease the reflection losses on the interface of ITO with the neighbor layers.…”
Section: Introductionmentioning
confidence: 99%